2017
DOI: 10.1111/iwj.12860
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and patient burden in patients with split‐thickness skin graft donor site wounds

Abstract: Split-thickness skin grafting is a common procedure to treat different kinds of wounds. This systematic, multicentre, observational, cross-sectional study of adult patients with split-thickness skin graft (STSG) donor site wounds was conducted to evaluate quality of life (QoL) impairments caused by donor site wounds following split-thickness skin grafting. Therefore, 112 patients from 12 wound centres in Germany were examined based on patient and physician questionnaires as well as a physical examination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…STSG has become one of most used technique to treat skin loss due to various reasons. Burns are considered one of major reasons [15]. In this study the majority (95%) of cases were due to burns that resulted in full skin loss and necessitate coverage by STSG.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…STSG has become one of most used technique to treat skin loss due to various reasons. Burns are considered one of major reasons [15]. In this study the majority (95%) of cases were due to burns that resulted in full skin loss and necessitate coverage by STSG.…”
Section: Discussionmentioning
confidence: 75%
“…In one survey patients reported an average of 15.6 up to 33.8 days they could not go to work due to the donor-site wound. 15 The using of nano fat graft was not only beneficial in decreasing healing time of donor area but it was responsible for a better epithelial thickness (Fig. 7).…”
Section: Discussionmentioning
confidence: 95%
“…Humrich and colleagues13 conducted a multicenter, observational, cross-sectional study of 112 adult patients with split-thickness skin graft (STSG) donor-site wounds to evaluate HRQoL related to acute donor-site wounds following split-thickness skin grafting. Most indications for skin grafting were postsurgical treatment (n = 51; 42.5%) and chronic wounds (n = 47; 39.2%) 12.…”
Section: Discussionmentioning
confidence: 99%
“…Donor site pain is one of the most distressing symptoms reported by skin graft patients in the early postoperative period 15 and is reported to impair patients' everyday activities. 16 Several publications discuss the management of donor site wound care but fail to appropriately document the pain related to the harvesting of STSGs and FTSGs. It has been suggested that patients have difficulty reporting their donor site-related pain likely due to their perception of pain from the primary wound.…”
Section: Discussionmentioning
confidence: 99%